The role of galectin-1 and galectin-3 in the mechanisms of T-cell immune response dysregulation in colon cancer - V. S. Poletika; Yu. V. Kolobovnikova; O. I. Urazova; O. A. Vasileva; A. I. Dmitrieva; K. I. Yankovich; V. V. Novitsky; L. M. Ryabova; M. Yu. Grishchenko (Бюллетень сибирской медицины)
The aim of the study was to characterize the features of the subpopulation composition and cytokine-secretory activity of T lymphocytes (Th1, Th17 and Treg) in relation to the concentration of galectin-1 and galectin-3 in the blood of patients with colon cancer.Materials and methods. A total of 26 patients diagnosed with colon cancer were examined. The study material included whole peripheral blood, blood plasma, and supernatants of suspension cultures of mononuclear leukocytes. Lymphocytes isolated from blood were typed by flow cytometry using monoclonal  antibodies. The content of galectin-1 and galectin-3 (in blood plasma) and IFNγ, IL-17A, and TGFβ (in supernatants of mononuclear leukocyte culture in vitro) were determined by enzyme-linked immunosorbent assay. The results obtained were analyzed by statistical methods.Results. In patients with colon cancer, a significant increase in the concentration of galectin-1 and galectin-3 in the blood plasma was found, which was associated with a decrease in the content of CD4+T-bet+ Th1 lymphocytes, CD4+RORC2+ Th17 lymphocytes in the blood and in vitro hyposecretion of IL-17. At the same time, positive correlations were revealed between the concentration of galectin-1 and galectin-3, the content of CD4+FoxP3+ Treg cells in the blood, and the secretion of TGFβ by mononuclear leukocytes in vitro.Conclusion. In colon cancer, increased levels of galectin-1 and galectin-3 in the blood are associated with quantitative deficiency and inhibited secretory activity of effector T lymphocytes and activation of the immunosuppressive functions of regulatory T cells. These results suggest a negative role of galectin 1 and galectin 3 in the mechanisms of regulation of the T cell immune response in colon cancer.